Large-scale assessment on civic and citizenship education: historical perspectives and future research developments - Damiani, Valeria; Losito, Bruno; Sanzo, Alessandro (Rivista di Storia dell’Educazione, 2018)
Since the Seventies international large-scale assessments carried out by IEA (International Association for the Evaluation of Educational Achievement) have significantly contributed to educational research, in terms of definition of theoretical constructs, methods for developing achievement tests, enhancement of data analysis techniques and creation of indicators, in order to examine and compare different education systems in the world. Since the second half of 1990s, in addition to IEA, also the OECD (Organization for the Economic Co-operation and Development) organizes and manages international comparative studies. This institution carried out international surveys related to either school education (i. e. PISA, Programme for International Student Assessment, which represents the most relevant study) or adult education (starting from the IALS and SIALS projects to the recent PIAAC project, Programme for the International Assessment of Adult Competencies). This paper firstly aims at retracing, from an historical point of view, IEA and OECD large-scale assessments development, analysing the similarities and the differences in the planning and managing of the surveys with regard to the conceptual background, the adopted methodologies and tools and the use of results. Starting from this preliminary historical analysis, this contribution then examines international large-scale assessments on civic and citizenship education carried out by the IEA, from the First Civic Education Study (1970-1971) to the ICCS 2016 (International Civic and Citizenship Education Study), whose results have been released in November 2017. This review allows reflecting on the development over time of the theoretical frameworks, of the survey methodologies and tools of the IEA international comparative research. This analysis tackles aspects related both to the specific field of civic and citizenship education and more in general to other surveys conducted by the organisation in different areas of school education (reading, maths and science, ICT). The overall aim of this investigation is to highlight the specific and significant contribution provided by international large-scale assessments in the scrutiny of education, both in relation to national curricula and school and classroom contexts.